A Patient with an Unusual Circulating Anticoagulant - Biggs, Rosemary; Denson, K. W. E; Nossel, H. L (Thrombosis and Haemostasis, 1964)
The investigation of a patient with an inhibitor which destroyed factor VIII is described. The inhibitor was active at high dilution but inactivated only 70–80 per cent of added factor VIII if tested by a two-stage assay method. Using a one-stage method 90–95 per cent of the activity disappeared. Thus, according to the method used, 5–30 per cent of factor VIII remained in the patient’s plasma. No other type of inhibitor was detected, yet the whole blood clotting time was prolonged and experience with haemophilic patients suggests that factor VIII levels between 5 and 30 per cent of normal should be accompanied by normal clotting time.